The effect of natural and man-made disasters on countries' production efficiency - George Halkos; Shunsuke Managi; Nickolaos Tzeremes (Journal of Economic Structures, 2015)
This study intends to understand how disaster is related to countries' production efficiency using a sample of 137 countries over 1980 - 2011. We analyze the effect of the number of man-made and natural disaster occurrences on countries' technological change (swift of the frontier) and technological catch-up (distribution of efficiencies). The results reveal an inverted "U" shape relationship between countries' technological change and technological catch-up with disaster occurrences. This finding suggests that the effect on countries' production efficiency is positive for lower number of disaster events; however, after a specific threshold value, the effect becomes negative. The results also reveal that low-income countries are negatively affected much quicker compared to high-income countries. Finally, it is evident that the negative effect of disaster occurrences impacts first countries' technological catch-up and then their technology change.
Keywords: C14; D24; O47; 330; Disasters; Production efficiency; Conditional efficiency; Nonparametric analysis